Numerical Heat Transfer Investigation in a Solar Receiver Heat Exchanger Channel with Punched Elliptical-Winglet Vortex Generators - Pitak Promthaisong; Pongjet Promvonge; Chitakorn Khanoknaiyakarn; Sompol Skullong (My University, 2021)
Thermal performance in a solar receiver heat exchanger (SRX) channel with punched elliptical-winglet vortex generator (P-EW) mounted on the absorber plate is numerically examined for Reynolds number (Re) ranging from 4000 to 24,000.In the present simulation, the P-EW characteristics included three ratios of winglet pitches (P R = 2.0, 1.5 and 1.0) including four sizes of the perforated-holes (nondimensional hole diameter, d R = 0.0, 0.25, 0.417 and 0.583) at one value of the attack angle ( =30°) and relative height (B R = 0.48).The computation reveals that employing P-EW generally yields considerably large friction factor (f) and Nusselt number (Nu) than the flat-plate channel alone.The use of smaller hole size causes the rise in Nu and f.It is noticeable that counter-spinning vortices pairs generated by the multiple P-EW can induce the impinging flow onto the absorber plate together with the air jet coming out of the hole, leading to the rise in the heat transfer rate greater than the smooth flat-plate channel.The highest thermal performance of about 1.9 was seen for the one with P R = 1.5 and d R = 0.417.
Keywords: Wingtip device; Vortex generator; Heat Transfer and Optimization